Prevalence of celiac disease in adult type 1 patients with diabetes - Dogan, Burcu (Pak J Med Sci, 2015)
OBJECTIVES: Celiac disease, an autoimmune disease, is related to immune mediated intolerance to gluten. Some studies suggest that Celiac Disease was 20 times more frequent in type 1 patients with diabetes. The objective of our study was to evaluate the prevalence of celiac disease in hospital based type 1 diabetic adults. METHODS: Our study was carried out retrospectively in Medeniyet University Goztepe Training and Educational Hospital in Istanbul between 2012–2013. The cohort comprised 482 type 1 patients with diabetes attending the diabetes outpatient clinic. The data were analyzed by SPSS 10.5 package program. Student’s t tests is used for comparative analyses. A p-value less than 0.05 was considered statistically significant. RESULTS: The cohort included 482 type 1 patients with diabetes. Fifty seven of them were not evaluated for Endomysium antibody positivity. Fifteen of the remaining 425 patients were positive for anti endomysial antibody (3.5%). The prevalence of biopsy proven celiac disease was 2.3% (10/425). There was no significant difference between Endomysial antibody positive and negative groups in regard of age, sex, or duration of the disease. CONCLUSION: This study confirms that the celiac disease is common in type 1 diabetic patients. Since a small proportion of celiac patients are symptomatic this disorder should be screened in all adult type 1 patients with diabetes by antiendomysium antibody.